2020
DOI: 10.1080/13562517.2020.1863349
|View full text |Cite
|
Sign up to set email alerts
|

How do learning technologies impact on undergraduates’ emotional and cognitive engagement with their learning?

Abstract: This is a repository copy of How do learning technologies impact on undergraduates' emotional and cognitive engagement with their learning?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…For example, there are studies exploring on emotional health and resilience (Lenzo, et. al., 2020), physical well-being (Fernandez-Ozcorta et al, 2019), homelessness (Barnes et al, 2018), suicide (Kakunje et al, 2020;Arrivillaga et al, 2020), mental health (Browning et al,, & LaValle, 2020;Gibbons et al, 2019;Langsi, 2021), negative emotional eating (Sze, Lee, Chan, & Kim, 2021), emotional intelligence and academic success (Suleman et al, 2019), daily stress, anxiety, empathy and coping (Montero & Morales-Rodriguez, 2021), posttraumatic growth (Thomas et al, 2020), cognitive engagement and learning (Venn, Park, Andersen, & Hejmadi, 2020), social competencies (Kaur et al, 2021) and coping styles (Song, 2020). These studies demonstrated that human emotional experience has a great impact on individuals' overall life and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are studies exploring on emotional health and resilience (Lenzo, et. al., 2020), physical well-being (Fernandez-Ozcorta et al, 2019), homelessness (Barnes et al, 2018), suicide (Kakunje et al, 2020;Arrivillaga et al, 2020), mental health (Browning et al,, & LaValle, 2020;Gibbons et al, 2019;Langsi, 2021), negative emotional eating (Sze, Lee, Chan, & Kim, 2021), emotional intelligence and academic success (Suleman et al, 2019), daily stress, anxiety, empathy and coping (Montero & Morales-Rodriguez, 2021), posttraumatic growth (Thomas et al, 2020), cognitive engagement and learning (Venn, Park, Andersen, & Hejmadi, 2020), social competencies (Kaur et al, 2021) and coping styles (Song, 2020). These studies demonstrated that human emotional experience has a great impact on individuals' overall life and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…One of the paramount challenges that educators face, especially in the realm of teaching ELLs, is addressing and bridging the gaps in prior knowledge (Arokiyaraj et al, 2021). These gaps can vary signi cantly, stemming from diverse cultural backgrounds, differing educational systems, or even individual life experiences (Venn et al, 2020). Navigating these can often dictate the trajectory of a student's learning experience.…”
Section: Bridging Prior Knowledge Gapsmentioning
confidence: 99%
“…complexities of teaching, especially in the context of ELLs, demand not only profound knowledge but also a repertoire of cognitive strategies to facilitate effective learning (Howson & Kingsbury, 2021). Cognitive strategies represent a set of techniques or tools that teachers consciously employ to assist, enhance, or optimize the learning process(Venn et al, 2020). Delving into the cognitive strategies adapted by teachers provides insights into the multifaceted world of pedagogy, offering a clearer picture of how educators mentally maneuver their way through the teaching landscape(Conto et al, 2021).…”
mentioning
confidence: 99%
“…There is a lack of consensus about which data might really relate to student engagement as well as the extent to which that data can be captured by LA (Bassett-Dubsky, 2020). Even the concept of student engagement is a contentious construct (Venn, Park, Palle-Anderson, & Hejmadi, 2020), often driven by availability of data (Bond, Buntins, Bedenlier, Zawacki-Richter, & Kerres, 2020;Dyment, Stone, & Milthorpe, 2020) rather than framing student experiences in ways that make sense to a diversity of individual students (Broughan & Prinsloo, 2020). If the data collated acts to create a singular construct of student engagement (Bassett-Dubsky, 2021), this disempowers students and further marginalises those who already believe they do not align with perceived norms of who belongs and how to belong in HE (Broughan & Prinsloo, 2020).…”
Section: Introductionmentioning
confidence: 99%